2012
DOI: 10.1089/met.2011.0087
|View full text |Cite
|
Sign up to set email alerts
|

A Gender-Stratified Comparative Analysis of Various Definitions of Metabolic Syndrome and Cardiovascular Risk in a Multiethnic U.S. Population

Abstract: We found the newly defined consensus criteria for metabolic syndrome to be similarly predictive of cardiovascular events when compared to existing definitions. Significant gender differences exist in the association between metabolic syndrome, its individual components, and CVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 34 publications
(36 reference statements)
3
15
0
Order By: Relevance
“…These results confirmed previous findings in Tunisian population [5][6][7]17 as well as in others population [18][19][20][21] . Sedentary lifestyle, the lack of participation in physical activities among adult Tunisian women, hormonal factors and postmenopausal weight gain may prove the large waist circumference in women 22,23 .…”
Section: Discussionsupporting
confidence: 93%
“…These results confirmed previous findings in Tunisian population [5][6][7]17 as well as in others population [18][19][20][21] . Sedentary lifestyle, the lack of participation in physical activities among adult Tunisian women, hormonal factors and postmenopausal weight gain may prove the large waist circumference in women 22,23 .…”
Section: Discussionsupporting
confidence: 93%
“…Most studies have reported the presence of gender differences in the prevalence of MetS components [57, 14, 21, 22]. However, the gender-specific differences in characteristics are not consistent across studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, whether these sex related differences in metabolic profiles are associated with a differential risk for Type 2 diabetes, CVD and overall mortality, is not clearly known [71]. While there are studies that support the notion of differential risk based on the combination of MetS components [72], to our knowledge, only a very few sex specific analyses of CVD and mortality risk in patients with MetS have been described [71,73]. Future studies from large community-based investigations should help better understand this concept of differential risk in MetS, as it is an important consideration when designing risk reduction strategies.…”
Section: Clinical Implication Of Sex Differencesmentioning
confidence: 99%